Critical success factors, issues and concerns in tourism sustainability - Yong Enn Lun (Pearson Malaysia Sdn Bhd, 2013)
According to the endogenous growth theory, innovation is the essential element for economic growth. There are arguments about how one economy can best absorb the benefits from innovation from various sectors. In a broad sense, the theory provides elaboration about the mechanism that links innovation and economic growth. Into the future, the theory predicts how people will be benefited through surging forward a standard of living incorporated with innovative production. The ongoing arguments, however, believe some other factors are indeed playing the complementarily role so that the economy can reap the prosperity out of innovation in an optimum manner. The tourism itself is an innovative sector. By focusing in BIMP-EAGA with a different economic model specification, the study aims at the empirical uniqueness of countries in the BIMP-EAGA in terms of the nexus between infrastructure investment in the form of ICT and tourism sector development. The results of causal relationship are arranged in such a way to show that ICT is a direct platform for more innovation development, which directly contributes to tourism development. Further studies are recommended for this issue due to the imperative role of infrastructure investment found, which is seen to have insignificant role in explaining economic growth in the literature.